Computational Analysis of Street Vendor and Pedestrian Interactions in Lagankhel, Nepal - Bal, Minu Lama; Salike, Inu Pradhan (Journal of Engineering Issues and Solutions, 2025)
Street vendors play an important role in urban economy of developing countries, including Nepal. Regardless their contribution to accessibility, affordability, and social vibrancy, they are often excluded from the spatial planning. Many researchers fail to catch the adaptive, informal and interactive nature of street vending, notably in relation to pedestrian movement and behavior. This study investigates the spatial and social dynamics between street vendors and pedestrian in dense urban setting of Lagankhel, Nepal, through computational tools. This study investigates the spatial arrangement and social interaction between street vendor and pedestrian through using computational tool. This research was conducted in the Lagankhel area of Lalitpur, a busy marketplace where both vendor activity and pedestrian flow intensify during the evening peak hours. Field observations were combined with parametric simulations: Isovist analysis was used to examine spatial visibility, while PedSim was simulated the pedestrian movement flow and stopping behavior. Data were collected across four urban zones to assess vendors positioning, visibility and interaction duration. Findings show that street vendors tend to occupy spaces with greater visual openness and spatial permeability, particularly near nodes of natural pedestrian slowdown or congregation. Pedestrians were observed to pause more frequently in areas with higher visibility catchment. These spatial behaviors highlight the adaptive strategies of vendors and the informal logic underlying their placement. Computational outputs showed that dense clustering of vendors reduced pedestrian flow efficiency, while clearer sightlines improved spatial legibility. These results support the development of inclusive planning frameworks that account for the dynamics of street vending without undermining pedestrian accessibility